The politics of land value taxation - McLean, I (Oxford University Press, 2018)
This chapter aims to show that land value tax has both theoretical and practical merit. The author traces the classical normative arguments for land tax in Adam Smith, Tom Paine, David Ricardo, Henry George, and Lloyd George, and the current academic literature, and then shows how some of difficulties of inheritance (estate) tax can be resolved by a land tax. It would also improve on the UK’s current ragbag of property taxes. In the final sections, issues of practicability, and of winners and losers, are addressed. The examples almost all come from the United Kingdom, but the arguments are intended to be general.